2015
DOI: 10.1136/bjophthalmol-2015-307168
|View full text |Cite
|
Sign up to set email alerts
|

Management of choroidal naevomelanocytic lesions: feasibility and safety of a virtual clinic model

Abstract: In this pilot study, a streamlined, dedicated, virtual service for rapid assessment (within 2 weeks of referral) of choroidal naevomelanocytic lesions was shown to be feasible and safe. Such a model of service delivery may prove cost-efficient while optimising patient experience. Further prospective studies are required for formal validation of the proposed service model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…The last decade has seen advances in multimodal ocular imaging and in telemedicine platforms, allowing innovative delivery of care in several ophthalmic sub-specialties [ 1 , 2 , 3 , 4 , 5 ], including oncology [ 6 , 7 , 8 ]. This technology enhances opportunities for the remote monitoring of melanocytic choroidal tumors of uncertain malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…The last decade has seen advances in multimodal ocular imaging and in telemedicine platforms, allowing innovative delivery of care in several ophthalmic sub-specialties [ 1 , 2 , 3 , 4 , 5 ], including oncology [ 6 , 7 , 8 ]. This technology enhances opportunities for the remote monitoring of melanocytic choroidal tumors of uncertain malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…This represents a high level of lesion awareness, appropriate detection and referral practices and improved diagnostic techniques among the practising clinicians utilising the centre . Similarly, substantial agreement in the clinical management decisions regarding melanocytic fundus lesions by optometrists compared with ophthalmological opinion has been reported elsewhere …”
Section: Discussionmentioning
confidence: 85%
“…One other group has previously utilized teleophthalmology as a virtual platform to assess new referrals for melanocytic lesions. Balaskas et al [10] evaluated a virtual service for rapid assessment of these patients and concluded that this platform may be feasible, safe, and cost-effective.…”
Section: Discussionmentioning
confidence: 99%